2019
DOI: 10.1055/s-0039-3399577
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastographic Evaluation of the Lower Lateral Nasal Cartilage Lateral Crus, Auricular Conchal Cartilage, and Costal Cartilage

Abstract: We investigated the sonoelastographic features of the lower lateral nasal cartilage lateral crus (LLNC-LC), auricular conchal cartilage (ACC), and costal cartilage (CC). In this prospective study, group 1 consisted of 60 participants (30 males and 30 females) between 18 and 35 years of age. Group 2 consisted of 60 participants (30 males and 30 females) between 35 and 50 years of age. Strain elastography (SE) and shear wave elastography (SWE) were performed. For all LLNC-LCs and ACCs, type I SE was detected mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It is difficult to directly compare the present findings to those from previous studies of measurement. The range of elastic modulus from the results of this study was similar to a recent study [ 22 ]. This study attempted to quantify the elastic properties of auricular conchal cartilage, nasal cartilage, and costal cartilage using SWE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is difficult to directly compare the present findings to those from previous studies of measurement. The range of elastic modulus from the results of this study was similar to a recent study [ 22 ]. This study attempted to quantify the elastic properties of auricular conchal cartilage, nasal cartilage, and costal cartilage using SWE.…”
Section: Discussionsupporting
confidence: 91%
“…It is widely used for muscles, ligaments, and tendons [ 21 ]. One recent study has demonstrated that SWE is a feasible method for quantifying the elastic properties of lower lateral nasal cartilage, costal cartilage, and conchal cartilage [ 22 ]. Few studies have been conducted to investigate the specific-regional elastic properties of distal FAC.…”
Section: Introductionmentioning
confidence: 99%
“…24 Sonoelastographic studies suggest use of auricular conchal cartilage for primary and revision rhinoplasties given that its shear wave elastography profile is most similar to that of the lower lateral nasal cartilage, whereas costal cartilage should only be used for nasal dorsum augmentation given its higher shear wave elastography profile. 25 Lastly, utilization of any cartilage grafts for late reconstruction does not increase risk of adverse events (P = 0.597). This remained true when comparing ear versus rib cartilage for late reconstruction (P = 0.394).…”
Section: Discussionmentioning
confidence: 96%
“…Advantages of ear cartilage include its convenient harvest from a relatively local additional surgical site, but its disadvantages include decreased stiffness precluding its use for substantial structural support 24. Sonoelastographic studies suggest use of auricular conchal cartilage for primary and revision rhinoplasties given that its shear wave elastography profile is most similar to that of the lower lateral nasal cartilage, whereas costal cartilage should only be used for nasal dorsum augmentation given its higher shear wave elastography profile 25. Lastly, utilization of any cartilage grafts for late reconstruction does not increase risk of adverse events ( P =0.597).…”
Section: Discussionmentioning
confidence: 99%